Introduction to Youth Online Peer Support: A Guide for Parents and Caregivers: FCS3396/FY1538, 1/2024 - Nielsen, Angela; Forthun, Larry (EDIS, 2024)
The purpose of this publication is to inform the reader about online friendships between teens, mental health and suicidality in teens, ideas for supporting a teen whose online friend discloses thoughts of self-harm and suicide, and the importance of safety and self-care. Written by Angela Nielsen and Larry F. Forthun, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.